PERCEPTION AND PERFORMANCE OF INTERCULTURAL COMMUNICATION COMPETENCE THROUGH USING ENGLISH AS A GLOBAL LANGUAGE : A CONTEXT OF SECOND-YEAR FAST TRACK STUDENTS AT FELTE, ULIS, VNU = Nghiên cứu về nhận thức và cách thể hiện năng lực giao tiếp liên văn hóa thông qua sử dụng tiếng Anh toàn cầu của sinh viên chất lượng cao năm thứ hai tại khoa sư phạm tiếng Anh, trường ĐHNN, ĐHQG Hà Nội - Trương, Thị Thu Thảo (2020)
Due to one of the primary attempts to raise an awareness of intercultural communication, the paper aims at investigating the perception of intercultural communication competence as well as the performance of English as a global language of the second-year fast-track students in class 13E1. To fulfill this ultimate purpose, qualitative method with two research instruments including questionnaires and observations were adopted. The participants of the study were 20 second-year students of Fast-track Program. The most significant findings of the paper were that despite the current trend on preference of native-likeness when communicating in English, the second-year fast-track students had positive perception of intercultural communication competence and demonstrated appropriate performance of English as a global language. The study, therefore, would serve as a good reference for both English language teachers and foreign language specialized students who desire to get more knowledge of this issue and develop international sense